Silicone resin, preparation method and application thereof

By preparing cross-type silicone resin with end groups of alicyclic epoxy functional groups and using UV cation curing mechanism, the oxygen polymerization problem in UV radical curing three-proof paint and the insufficient protection effect of traditional silicone resins in high temperature environments is solved, and a silicone resin with high cross-linking density and high temperature resistance is achieved.

CN115926170BActive Publication Date: 2025-03-18NINGBO RUNHE HIGH TECH MATERIAL CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211597597.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-03-18
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The existing UV radical curing triple-proof paint has technical obstacles to oxygen-resistance polymerization, and traditional thermally cured silicone resins have limited protection effects on integrated circuits and electronic components in high temperature environments.

Method used

A cross-type silicone resin with end groups of alicyclic epoxy functional groups is prepared by polycondensation, decompression, catalysis and removal steps, combined with the UV cation curing mechanism, a silicone resin with high cross-linking density and three-dimensional network structure is formed.

Benefits of technology

It improves the cross-linking density and curing degree of silicone resin, provides better protection against integrated circuits and electronic components, and has better high temperature resistance, broadening its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115926170B_ABST
    Figure CN115926170B_ABST
Patent Text Reader

Abstract

The present application discloses a silicone resin, and a preparation method thereof includes a polycondensation step, a decompression step, a catalysis step, and a removal step. The silicone resin prepared in the present application is used to make a three-proof paint, which can be cured through a UV cationic mechanism to form a three-dimensional network structure, thereby improving the crosslinking density and the degree of curing, and at the same time can give the packaged integrated circuits and electronic components a higher operating temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and specifically to a silicone resin, a preparation method and an application thereof. Background Art

[0002] Silicone resin is one of the main categories of organosilicon products. Although it is the earliest to appear among all organosilicon materials, its varieties are relatively few and its market share is also small. The main use of silicone resin is to prepare various electrical insulating paints, weather-resistant coatings, plastic surface wear-resistant coatings and high-temperature resistant coatings. In addition, silicone resin is also used as mica adhesives, asbestos cloth glass cloth impregnation paint, concrete and masonry waterproofing agents, etc., and is also widely used in aerospace, electronics, construction, machinery manufacturing and other fields.

[0003] Traditional silicone resins are generally prepared by hydrolysis, polycondensation and other steps in a mixed solvent using a mixture of organic chlorosilanes or organic alkoxysilanes as raw materials. Affected by the steric hindrance of silicone resins and the entanglement and wrapping of polymer molecular chains, the silicone resin molecules prepared by the above process inevitably contain a certain number of silanol groups. The presence of these silanol groups hinders the silicone resin from further forming a high molecular weight, highly cross-linked network structure during the hydrolysis and polycondensation process. Therefore, the silicone resin prepared by hydrolysis and polycondensation is usually called a prepolymer. Silicone hydroxyl groups are a significant feature of these incompletely cross-linked silicone resin prepolymers. Under heating or the action of a catalyst, the silicone resin prepolymer gradually transforms into a thermosetting resin with a three-dimensional network structure, insoluble and infusible, and highly cross-linked. This process is essentially the curing process of silicone resin. Therefore, silicone resins generally need to be further condensed and polymerized at high temperatures, and the silicone resins are cured and formed while removing the generated water. Since thermal condensation curing requires a high temperature and a long time, the traditional curing method limits the application range of silicone resins for some occasions that require use in normal temperature or low temperature environments and require rapid curing.

[0004] Using tetrafunctional organosilicon monomers such as SiCl4 or Si(OR)4 (R is methyl or ethyl) as raw materials, a Q-linked (SiO 4 / 2) structured silicone resin, adding monofunctional (M chain segment) chlorosilane or alkoxysilane to the reaction monomers at the same time, a series of MQ type silicone resins can be prepared, such as trimethylsiloxy-terminated methyl MQ resin, dimethylvinylsiloxy-terminated methylvinyl MQ resin, dimethylhydrogensiloxy-terminated methylhydrogen MQ resin, dimethylphenylsiloxy- or methyldiphenylsiloxy-terminated methylphenyl MQ resin, methylphenylvinylsiloxy-terminated methylphenylvinyl MQ resin, etc. Adding difunctional (D chain segment) dichlorosilane or dialkoxysilane to the raw materials for preparing MQ type silicone resins, a similar co-hydrolysis and polycondensation method can be used to prepare MDQ type silicone resins. In addition, similar processes can be used to prepare silicone resins containing different types of chain segments such as MDT, MT, DT, and MDTQ, which are widely used in the fields of silicone encapsulation, filler reinforcement, and surface interface adhesion.

[0005] Conformal paint with moisture-proof, salt spray-proof and mildew-proof functions is an important packaging and protection material for integrated circuits or components. It is a functional material that provides insulation, heat resistance, weather resistance, wear resistance and other coating protection for precision circuit boards. It was originally mainly used in high-tech industries, but with the increasing advancement of electronic technology, conformal paint has gradually been used in the field of daily electrical appliances. Conformal paints such as 1B73 from Humiseal of the United States, CRC70 from CRC of the United States, 1-2577 from Dow Corning of the United States, and AFA-F from Erigol of the United Kingdom are the earliest foreign-funded products in the Chinese market. Among them, Humiseal 1B73, CRC70 and Erigol AFA-F are all acrylic conformal paints, and Dow Corning 1-2577 is a solvent-based silicone resin conformal paint. These conformal paints can be cured and formed by heating.

[0006] Since integrated circuits and electronic components are sensitive to thermal environments, the use of temperature-increasing curing can easily damage electronic components, which in turn leads to the failure of integrated circuits and electronic components. In order to overcome the defects of heat-curing conformal coatings that use organic solvents and require heating for curing, UV-curing conformal coatings have gradually entered the application field in recent years, such as the D959 series UV glue developed by Zhongshan Sangu Electronic Materials Co., Ltd., SF-577 developed by Shenzhen Android Electronic Materials Co., Ltd., and UV-curing conformal coating 5002 produced by Yongyue Technology Co., Ltd. However, these UV-curing conformal coatings are mostly acrylic or epoxy resins, with low operating temperatures, which cannot meet the needs of high-temperature applications. In addition, existing UV-curing conformal coatings are mostly free radical curing systems, which require high vacuum and nitrogen protection when used to eliminate the adverse effects caused by oxygen inhibition.

[0007] Since the Si-O-Si bond in the organosilicon material molecule has a higher bond energy than the CC bond and the CO bond, the organosilicon material has a more excellent high temperature resistance. In addition, the Si-O-Si bond has a helical structure, and the use of organosilicon materials as packaging materials is conducive to reducing internal stress and avoiding the failure of integrated circuit and electronic component packaging. Therefore, the introduction of alicyclic epoxy functional groups into organosilicon molecules can obtain organosilicon packaging materials that can be rapidly formed using a UV cationic curing mechanism at room temperature. This UV cationic curing organosilicon packaging material not only overcomes the technical drawbacks of oxygen inhibition during UV free radical curing, but also avoids the energy consumption and high temperature adverse effects on devices caused by thermal curing.

[0008] In 2012, Sophie Putzien et al. (Journal of Applied Polymer Science, 2012, 126: 1188-1197) disclosed a method for preparing aliphatic epoxy or alicyclic epoxy terminated polysiloxane. They used double-terminated hydrogenated silicone oil with molecular weights of 580 and 680 and 1,1,3,3,5,5-hexamethyltrisiloxane as raw materials, 1,4-butanediol divinyl ether, triethylene glycol divinyl ether, 1,3-diisopropenylbenzene and 1,9-decadiene as organic spacer groups, allyl glycidyl ether and 4-vinyl-1,2-epoxycyclohexane as end-capping groups, and prepared the obtained polysiloxane through two hydrosilylation reactions. These aliphatic or alicyclic epoxy group-modified polysiloxanes can obtain cross-linked UV coatings under the action of cationic UV photocuring initiators. Since the silicone polymers used are linear polymers with low cross-linking density, the resulting materials are soft, elastic and transparent films with poor mechanical properties, making it difficult to achieve effective packaging of integrated circuits. Summary of the invention

[0009] The purpose of the present application is to overcome the technical obstacle of oxygen inhibition in the existing three-proof coatings using UV free radical curing mechanism, and to improve the crosslinking density and curing degree of silicone resin.

[0010] In order to achieve the above purpose, the technical solution adopted in the present application is: to provide a silicone resin, the structural formula of which is shown in the following formula (I):

[0011] (Ⅰ)

[0012] Where m is any positive integer from 0 to 50.

[0013] The present application also provides a method for preparing a silicone resin, comprising a polycondensation step, a decompression step, a catalysis step and a removal step:

[0014] The polycondensation step is: in an inert gas atmosphere, add polydimethylsiloxane, the structure of which is shown in the following formula (II), into a container, then add a solvent and a tetrafunctional organosilicon monomer to carry out a polycondensation reaction to obtain a crude precursor product.

[0015] (Ⅱ)

[0016] Where m is a positive integer from 0 to 50;

[0017] The decompression step is to remove the solvent and low molecular weight substances in the crude precursor product to obtain polysiloxane, the structure of which is shown in the following formula (III):

[0018] (III)

[0019] Where m is any positive integer from 0 to 50;

[0020] The catalytic step is: in the inert gas atmosphere, reacting the alicyclic epoxy reaction monomer containing a C=C double bond, the polysiloxane and the catalyst in a solvent to obtain a crude reaction product;

[0021] The removal step is: removing the solvent and small molecule impurities from the crude reaction product to obtain the silicone resin.

[0022] Preferably, in the polycondensation step, the mass ratio of the polydimethylsiloxane to the solvent is (0.30:1) to (0.85:1); the molar ratio of the polydimethylsiloxane to the tetrafunctional silicone monomer is (2.5:1) to (5.0:1).

[0023] As another preference, in the polycondensation step, the tetrafunctional organosilicon monomer is silicon tetrachloride.

[0024] As another preference, a molecular sieve is used in the decompression step to remove residual chloride ions, and the molecular sieve is a 4A type molecular sieve, and the amount of the molecular sieve used is 1% to 10% of the mass of the crude reaction product.

[0025] As another preference, an antioxidant is also added in the catalytic step, and the mass ratio of the antioxidant to the alicyclic epoxy reaction monomer containing a C=C double bond is (0.001:1) to (0.1:1).

[0026] As another preference, in the catalytic step, the mass ratio of the solvent to the alicyclic epoxy reaction monomer containing a C=C double bond is (10:1) to (40:1); the molar ratio of the polysiloxane to the alicyclic epoxy reaction monomer containing a C=C double bond is (0.15:1) to (0.40:1).

[0027] As another preferred embodiment, in the catalytic step, the catalyst is a platinum catalyst, and the ratio of the mass of the platinum atoms in the platinum catalyst to the mass sum of the polysiloxane and the alicyclic epoxy reaction monomer containing a C=C double bond is (5×10 -6 :1)~ (500×10 -6 :1).

[0028] Further preferably, the alicyclic epoxy reaction monomer containing a C=C double bond is a combination of one or more of 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-3-vinylcyclohexane, 3-(1-methylvinyl)-7-oxabicyclo[4.1.0]heptane, and 2-methyl-5-(1-methylvinyl)-7-oxabicyclo[4.1.0]heptane; an antioxidant is also added in the catalytic step, and the antioxidant is a combination of one or more of 2,6-di-tert-butyl-4-methoxyphenol, p-hydroxyanisole, phenothiazine, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0029] The present application also provides a conformal coating, comprising component A and component B, wherein component A is the above-mentioned silicone resin, and component B is a UV curing agent.

[0030] Compared with the prior art, the beneficial effects of this application are:

[0031] (1) The cross-shaped silicone resin with alicyclic epoxy functional groups at the end is cured by UV cationic mechanism to form a three-dimensional network structure of silicone resin, which has a higher cross-linking density and better curing degree than the linear polysiloxane cured product modified with aliphatic or alicyclic epoxy groups, and can provide better protection for integrated circuits and electronic components;

[0032] (2) The cross-shaped silicone resin with alicyclic epoxy functional groups at the end is cured by UV cationic mechanism to form a three-dimensional network structure of silicone resin. It has better high temperature resistance than the cured product of linear polysiloxane modified with aliphatic or alicyclic epoxy groups, and can give the packaged integrated circuits and electronic components a higher operating temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the H-NMR spectrum of the polysiloxane prepared in the decompression step of Example 1.

[0034] Figure 2 This is the hydrogen NMR spectrum of the silicone resin prepared in Example 1.

[0035] Figure 3 This is the NMR silicon spectrum of the silicone resin prepared in Example 1.

[0036] Figure 4This is the H-NMR spectrum of the polysiloxane prepared in the decompression step of Example 2.

[0037] Figure 5 This is the hydrogen NMR spectrum of the silicone resin prepared in Example 2.

[0038] Figure 6 This is the H-NMR spectrum of the polysiloxane prepared in the decompression step of Example 3.

[0039] Figure 7 This is the hydrogen NMR spectrum of the silicone resin prepared in Example 3.

[0040] Figure 8 This is the H-NMR spectrum of the polysiloxane prepared in the decompression step of Example 4.

[0041] Fig. 9 This is the hydrogen NMR spectrum of the silicone resin prepared in Example 4.

[0042] Fig.10 This is the H-NMR spectrum of the polysiloxane prepared in the decompression step of Example 5.

[0043] Fig.11 This is the hydrogen NMR spectrum of the silicone resin prepared in Example 5.

[0044] Fig.12 This is the TGA curve of silicone resin samples 1 to 5 under nitrogen atmosphere. DETAILED DESCRIPTION

[0045] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0046] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0047] The silicone resin of the present application is a cross-shaped silicone resin with an alicyclic epoxy functional group as the terminal group, and its structure is shown in the following formula (I):

[0048] (Ⅰ)

[0049] Where m is any positive integer from 0 to 50.

[0050] The present application also provides a method for preparing the silicone resin, which comprises a polycondensation step, a decompression step, a catalysis step and a removal step.

[0051] Polycondensation step: in an inert gas atmosphere, a four-necked flask with a mechanical stirrer, a thermometer and a constant pressure dropping funnel is set, and the temperature is set to the polycondensation temperature, α-dimethylhydride-ω-silanol lithium terminated polydimethylsiloxane is added to the four-necked flask, and the structure thereof is shown in the following formula (II), and then a solvent is added, and then a tetrafunctional organosilicon monomer is added dropwise to the four-necked flask. After the tetrafunctional organosilicon monomer is added dropwise, the polycondensation temperature is maintained for a period of time to obtain a crude precursor product;

[0052] (Ⅱ)

[0053] Where m is a positive integer from 0 to 50;

[0054] Decompression step: the crude precursor product is transferred to a low-boiling-point removal device, the pressure is reduced and the temperature is raised to the decompression temperature to remove the solvent and the excess tetrafunctional organosilicon monomer, and the decompression time is maintained. The low-boiling-point removal device is then lowered to room temperature, and the generated lithium chloride precipitate is filtered out to obtain a crude product filtrate, and low molecular weight substances are removed to obtain a clear and transparent polysiloxane with a terminal dimethylhydrogensiloxy group, the structure of which is shown in the following formula (III):

[0055] (III)

[0056] Where m is any positive integer from 0 to 50;

[0057] Catalytic step: under the protection of dry inert gas, a solvent, an alicyclic epoxy reaction monomer containing a C=C double bond, an alicyclic epoxy reaction monomer containing a C=C double bond and a catalyst are added into a reaction container, the temperature is raised to the catalyst activation temperature under stirring, and the activation time is maintained for a certain period of time, and then the cross-shaped polysiloxane prepared in the decompression step is dripped into the reaction container, the dripping time is controlled to a certain period of time, and after the dripping is completed, the catalytic temperature is maintained for a certain period of time to obtain a crude reaction product;

[0058] Removal step: The crude reaction product is cooled to room temperature and then transferred to a low-boiling-point removal device. Under the protection of an inert gas, the removal temperature and pressure are set to remove the solvent and other small molecule impurities to obtain a silicone resin represented by the structural formula (I).

[0059] Preferably, the tetrafunctional organosilicon monomer in the polycondensation step is silicon tetrachloride; and the solvent in the polycondensation step is preferably tetrahydrofuran.

[0060] Preferably, in the removal step, the crude product is adsorbed with a molecular sieve to remove chloride ions introduced by silicon tetrachloride.

[0061] Preferably, an antioxidant is also added in the catalytic step to prevent the silicone resin from being oxidized and discolored.

[0062] Preferably, the polydimethylsiloxane is preferably polydimethylsiloxane terminated with α-dimethylhydrogen-ω-silanol lithium, and its degree of polymerization m ranges from 0 to 50; the mass ratio of polydimethylsiloxane terminated with α-dimethylhydrogen-ω-silanol lithium to tetrahydrofuran is (0.30:1) to (0.85:1); the molar ratio of polydimethylsiloxane terminated with α-dimethylhydrogen-ω-silanol lithium to silicon tetrachloride is (2.5:1) to (5.0:1).

[0063] Preferably, the polycondensation temperature is 15 to 45°C, the addition time of silicon tetrachloride is 15 to 240 min, and the polycondensation time is 2 to 24 h.

[0064] Preferably, the operating pressure in the decompression step is -101.3 to -90.0 kPa, and the decompression temperature is 140 to 180° C.; the molecular sieve used for adsorption is type 4A molecular sieve, and the amount of the molecular sieve used is 1% to 10% of the mass of the crude product filtrate.

[0065] Preferably, the mass ratio of the added antioxidant to the alicyclic epoxy reaction monomer containing a C=C double bond is (0.001:1) to (0.1:1); the mass ratio of the added solvent to the alicyclic epoxy reaction monomer containing a C=C double bond is (10:1) to (40:1); the molar ratio of the added cross-shaped polysiloxane to the alicyclic epoxy reaction monomer containing a C=C double bond is (0.15:1) to (0.40:1); the ratio of the mass of the platinum atom in the platinum catalyst to the sum of the mass of the cross-shaped polysiloxane and the alicyclic epoxy reaction monomer containing a C=C double bond is (5×10 -6 :1) ~ (500×10 -6 :1).

[0066] Preferably, the catalyst activation temperature is 55-95°C, and the activation time is 0.25-4 h; the addition time of the cross-type polysiloxane is 0.2-4.0 h; the catalytic temperature maintained after the addition is 60-90°C, and the catalytic time is 2-6 h.

[0067] Preferably, the solvent in the catalytic step is toluene, ethylbenzene, p-xylene, o-xylene, m-xylene or one or more combinations of xylenes.

[0068] Preferably, the antioxidant is one or more combinations of 2,6-di-tert-butyl-4-methoxyphenol (BHT), p-hydroxyanisole (MEHQ), phenothiazine, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010).

[0069] Preferably, the alicyclic epoxy reactive monomer containing a C=C double bond is preferably one or more combinations of 1,2-epoxy-4-vinylcyclohexane (CASRN: 106-86-5), 1,2-epoxy-3-vinylcyclohexane (CAS RN: 123366-20-1), 3-(1-methylvinyl)-7-oxabicyclo[4.1.0]heptane (CAS RN: 357175-33-8), and 2-methyl-5-(1-methylvinyl)-7-oxabicyclo[4.1.0]heptane (CAS RN: 94268-62-9).

[0070] Preferably, the catalyst is a vinyl complex of platinum, ie, Karstedt's catalyst.

[0071] Preferably, the removal temperature is 90 to 150°C, and the removal pressure is -101.1 to -90 kPa.

[0072] Preferably, the inert gas is one or more of nitrogen, helium or argon; the moisture content of the inert gas is less than 500 ppm. More preferably, the inert gas is nitrogen.

[0073] The following provides a specific method for preparing silicone resin. Unless otherwise specified, the raw materials used in the present invention can be purchased from the market or are commonly used in the art. Unless otherwise specified, the methods in the following embodiments are all conventional methods in the art.

[0074] Example 1

[0075] Polycondensation step: Under the protection of dry nitrogen, set up a 250 mL four-necked flask with a mechanical stirrer, a thermometer and a constant pressure dropping funnel, start stirring and add 60 mL of tetrahydrofuran (THF) and 37.85 g (0.0375 mol) of α-dimethylhydrogen-ω-silanol lithium-terminated polydimethylsiloxane with an average molecular weight of 1010, whose polymer m=11.52, maintain the polycondensation temperature at 28 ° C, add 1.91 g (0.0112 mol) of silicon tetrachloride dropwise to the solution in the four-necked flask, and control the dropping time to be 100 min. After the silicon tetrachloride is added dropwise, rinse the silicon tetrachloride dropping container with 25 mL of tetrahydrofuran, flush all the remaining silicon tetrachloride into the reaction solution, and maintain the polycondensation time for 2 h to obtain a crude precursor product.

[0076] Decompression step: The crude precursor product was transferred to a 250 mL low-boiling-point removal device, and the device temperature was raised to 170 °C at -101.1 kPa to remove tetrahydrofuran and excess silicon tetrachloride in the crude precursor product. When no small molecules were distilled out of the device, the low-boiling point removal operation was stopped; after the material was cooled to room temperature, residual chloride ions were removed by filter pressing, and 1.89 g of pre-dried 4A molecular sieve was added to the filtrate to remove residual chloride ions. After filtration, 30.51 g of colorless, clear and transparent cross-type polysiloxane with a terminal dimethylhydrogensiloxy group was obtained, with a yield of 80.60%. Its H NMR spectrum is shown in the attached figure. Figure 1 As shown, 1 H NMR (400 MHz, Chloroform-d) δ=0.09 (s, 300H), δ=4.70 (s, 4H).

[0077] Catalytic step: under the protection of dry nitrogen, 20 mL of toluene, 0.01 g of 2,6-di-tert-butyl-4-methoxyphenol (BHT), 1.11 g of 1,2-epoxy-4-vinylcyclohexane and 0.60 g of a platinum catalyst having a platinum atomic content of 0.02 wt% were added to a 100 mL three-necked flask, the temperature was raised to 70 ° C while stirring, and the catalyst was activated for 0.5 h; 7.00 g (0.00187 mol) of the cross-shaped polysiloxane obtained in the decompression step was added dropwise to the three-necked flask, the dropping time was controlled to be 1 h, and the catalytic temperature was maintained at 70 ° C after the addition was completed. The reaction was stopped after catalysis for 3 h to obtain a reaction mixture.

[0078] Removal step: The reaction mixture was cooled to room temperature and then transferred to a low boiling point removal device. Under the protection of dry argon gas with a moisture content of less than 50 ppm, the removal pressure was -101.2 kPa, and the temperature was gradually raised to 130 °C. After the solvent was removed under reduced pressure and then cooled to room temperature, 7.00 g of amber cross-shaped silicone resin with alicyclic epoxy functional groups as the terminal group was obtained. The yield was 88.3%. Its H NMR spectrum ( 1 H NMR) and NMR Si spectra ( 29 Si NMR) are shown in the attached Figure 2 and attached Figure 3 shown. 1 HNMR (400 MHz, Chloroform-d): δ=0.05(s, 93H), δ=0.49(t, 2H), δ=1.82(m, 0.9H), δ=3.13(m, 1.3H); 29 Si NMR (125 MHz, Chloroform-d): δ=7.17 (M links, RMe2SiO 1 / 2 ), δ = -22.01 ~ -22.60 (D link, Me2SiO1 / 2 ), δ = -116.36 (Q link, SiO 4 / 2 ).

[0079] Example 2

[0080] Polycondensation step: Under the protection of dry nitrogen, set up a 250 mL four-necked flask with a mechanical stirrer, a thermometer and a constant pressure dropping funnel, start stirring and add 25 mL of tetrahydrofuran (THF) and 24.91 g (0.018 mol) of α-dimethylhydrogen-ω-silanol lithium-terminated polydimethylsiloxane with an average molecular weight of 1380, whose polymer m=16.5, maintain the polycondensation temperature at 22 ° C, add 1.15 g (0.0068 mol) of silicon tetrachloride dropwise to the solution in the four-necked flask, and control the dropping time to 60 min. After the silicon tetrachloride is added dropwise, rinse the silicon tetrachloride dropping container with 20 mL of tetrahydrofuran, flush all the remaining silicon tetrachloride into the reaction solution, and maintain the polycondensation time for 5 h to obtain a crude precursor product.

[0081] Decompression step: The crude precursor product was transferred to a 250 mL low-boiling-point removal device, and the device temperature was raised to 180 °C at -98.2 kPa to remove tetrahydrofuran and excess silicon tetrachloride in the crude precursor product. When no small molecules were distilled out of the device, the low-boiling point removal operation was stopped; after the material was cooled to room temperature, residual chloride ions were removed by filter press, and 1.53 g of pre-dried 4A molecular sieve was added to the filtrate to remove residual chloride ions. After filtration, 20.38 g of colorless, clear and transparent cross-type polysiloxane with a terminal dimethylhydrogensiloxy group was obtained, with a yield of 81.81%. Its H NMR spectrum is shown in the attached figure. Figure 4 As shown, 1 H NMR (400 MHz, Chloroform-d) δ=0.09 (s, 420H), δ=4.70 (s, 4H).

[0082] Catalytic step: under the protection of dry nitrogen, 25 mL of toluene, 0.0052 g of 2,6-di-tert-butyl-4-methoxyphenol (BHT), 0.92 g of 1,2-epoxy-4-vinylcyclohexane and 2.75 g of a platinum catalyst with a platinum atomic content of 0.02 wt% were added to a 100 mL three-necked flask, the temperature was raised to 75 ° C while stirring, and the activation was carried out for 0.5 h; 8.00 g (0.00153 mol) of the cross-shaped polysiloxane obtained in the decompression step was added dropwise to the three-necked flask, the dropping time was controlled to be 2 h, and the catalytic temperature was maintained at 75 ° C after the addition was completed. The reaction was stopped after catalysis for 5 h to obtain a reaction mixture.

[0083] Removal step: The reaction mixture was cooled to room temperature and then transferred to a low boiling point removal device. Under the protection of dry nitrogen gas with a moisture content of less than 100 ppm, the removal pressure was -99.7 kPa, and the temperature was gradually increased to 135 °C. After the solvent was removed under reduced pressure and cooled to room temperature, 7.73 g of amber cross-shaped silicone resin with alicyclic epoxy functional groups as the terminal group was obtained. The yield was 88.2%. Its H NMR spectrum ( 1 H NMR) as attached Figure 5 shown. 1 H NMR (400 MHz, Chloroform-d): δ=0.05 (s, 123H), δ=0.49 (t, 2H), δ=1.82 (m, 0.6H), δ=3.13 (m, 1.9H).

[0084] Example 3

[0085] Polycondensation step: Under the protection of dry nitrogen, set up a 250 mL four-necked flask with a mechanical stirrer, a thermometer and a constant pressure dropping funnel, start stirring and add 60 mL of tetrahydrofuran (THF) and 38.20 g (0.0205 mol) of α-dimethylhydrogen-ω-silanol lithium-terminated polydimethylsiloxane with an average molecular weight of 1862, whose polymer m=23, maintain the polycondensation temperature at 35 ° C, add 1.0 g (0.006 mol) of silicon tetrachloride to the solution in the four-necked flask, and control the dropping time to 90 min. After the silicon tetrachloride is added, rinse the silicon tetrachloride dropping container with 30 mL of tetrahydrofuran, flush all the remaining silicon tetrachloride into the reaction solution, and maintain the polycondensation time for 15 h to obtain a crude precursor product.

[0086] Decompression step: The crude precursor product was transferred to a 250 mL low-boiling-point removal device, and the device temperature was raised to 140 °C at -101.3 kPa to remove tetrahydrofuran and excess silicon tetrachloride in the crude precursor product. When no small molecules were distilled out of the device, the low-boiling point removal operation was stopped; after the material was cooled to room temperature, residual chloride ions were removed by filter pressing, and 0.66 g of pre-dried 4A molecular sieve was added to the filtrate to remove residual chloride ions. After filtration, 33.21 g of colorless, clear and transparent cross-type polysiloxane with a terminal dimethylhydrogensiloxy group was obtained, with a yield of 86.90%. Its H NMR spectrum is shown in the attached figure. Figure 6 As shown, 1 H NMR (400 MHz, Chloroform-d) δ=0.09 (s, 576H), δ=4.70 (s, 4H).

[0087] Catalytic step: under the protection of dry nitrogen, 35 mL of toluene, 0.05 g of 2,6-di-tert-butyl-4-methoxyphenol (BHT), 1.00 g of 1,2-epoxy-4-vinylcyclohexane and 0.98 g of a platinum catalyst with a platinum atomic content of 0.02 wt% were added to a 100 mL three-necked flask, the temperature was raised to 80 ° C while stirring, and the mixture was activated for 1 h; 12.00 g (0.00168 mol) of the cross-shaped polysiloxane obtained in the decompression step was added dropwise to the three-necked flask, the dropping time was controlled to be 3 h, the catalytic temperature was maintained at 80 ° C after the addition was completed, and the reaction was stopped after catalysis for 2 h to obtain a reaction mixture.

[0088] Removal step: The reaction mixture was cooled to room temperature and then transferred to a low boiling point removal device. Under the protection of dry nitrogen gas with a moisture content of less than 100 ppm, the removal pressure was -96.9 kPa, and the temperature was gradually increased to 130 °C. After the solvent was removed under reduced pressure and cooled to room temperature, 10.87 g of amber cross-shaped silicone resin with alicyclic epoxy functional groups as the terminal group was obtained. The yield was 84.7%. Its H NMR spectrum ( 1 H NMR) as attached Figure 7 shown. 1 H NMR (400 MHz, Chloroform-d): δ=0.05 (s, 190H), δ=0.49 (t, 2H), δ=1.82 (m, 0.3H), δ=3.13 (m, 1.8H).

[0089] Example 4

[0090] Polycondensation step: Under the protection of dry nitrogen, set up a 250 mL four-necked flask with a mechanical stirrer, a thermometer and a constant pressure dropping funnel, start stirring and add 50 mL of tetrahydrofuran (THF) and 35.80 g (0.0205 mol) of α-dimethylhydrogen-ω-silanol lithium-terminated polydimethylsiloxane with an average molecular weight of 2381, whose polymer m=30, maintain the polycondensation temperature at 25 ° C, add 0.83 g (0.0049 mol) of silicon tetrachloride dropwise to the solution in the four-necked flask, and control the dropping time to be 150 min. After the silicon tetrachloride is added dropwise, rinse the silicon tetrachloride dropping container with 20 mL of tetrahydrofuran, flush all the remaining silicon tetrachloride into the reaction solution, and maintain the polycondensation time for 9 h to obtain a crude precursor product.

[0091] Decompression step: The crude precursor product was transferred to a 250 mL low-boiling-point removal device, and the device temperature was raised to 160 °C at -100.3 kPa to remove tetrahydrofuran and excess silicon tetrachloride in the crude precursor product. When no small molecules were distilled out of the device, the low-boiling point removal operation was stopped; after the material was cooled to room temperature, residual chloride ions were removed by filter press, and 1.84 g of pre-dried 4A molecular sieve was added to the filtrate to remove residual chloride ions. After filtration, 30.66 g of colorless, clear and transparent cross-type polysiloxane with a terminal dimethylhydrogensiloxy group was obtained, with a yield of 85.60%. Its H NMR spectrum is shown in the attached figure. Figure 8 As shown, 1 H NMR (400 MHz, Chloroform-d) δ=0.09 (s, 745H), δ=4.70 (s, 4H).

[0092] Catalytic step: under the protection of dry nitrogen, 28 mL of toluene, 0.0051 g of 2,6-di-tert-butyl-4-methoxyphenol (BHT), 0.51 g of 1,2-epoxy-4-vinylcyclohexane and 0.60 g of a platinum catalyst having a platinum atomic content of 0.02 wt% were added to a 100 mL three-necked flask, the temperature was raised to 72 °C under stirring, and the mixture was activated for 1.5 h; 10.00 g (0.00108 mol) of the cross-shaped polysiloxane obtained in the decompression step was added dropwise to the three-necked flask, the dropping time was controlled to be 3 h, the catalytic temperature was maintained at 72 °C after the addition was completed, the reaction was stopped after catalysis for 3 h, and a reaction mixture was obtained.

[0093] Removal step: The reaction mixture was cooled to room temperature and then transferred to a low boiling point removal device. Under the protection of dry nitrogen gas with a moisture content of less than 100 ppm, the removal pressure was -97.9 kPa, and the temperature was gradually increased to 135 °C. After the solvent was removed under reduced pressure and cooled to room temperature, 8.67 g of amber cross-shaped silicone resin with alicyclic epoxy functional groups as the terminal group was obtained. The yield was 82.5%. Its H NMR spectrum ( 1 H NMR) as attached Fig. 9 shown. 1 H NMR (400 MHz, Chloroform-d): δ=0.05 (s, 201H), δ=0.49 (t, 2H), δ=1.82 (m, 0.5H), δ=3.13 (m, 1.6H).

[0094] Example 5

[0095] Polycondensation step: Under the protection of dry nitrogen, set up a 250 mL four-necked flask with a mechanical stirrer, a thermometer and a constant pressure dropping funnel, start stirring and add 70 mL of tetrahydrofuran (THF) and 39.20 g (0.01256 mol) of α-dimethylhydrogen-ω-silanol lithium-terminated polydimethylsiloxane with an average molecular weight of 3122, whose polymer m=40, maintain the polycondensation temperature at 18 ° C, add 0.62 g (0.00365 mol) of silicon tetrachloride dropwise to the solution in the four-necked flask, and control the dropping time to be 105 min. After the silicon tetrachloride is added dropwise, rinse the silicon tetrachloride dropping container with 30 mL of tetrahydrofuran, flush all the residual silicon tetrachloride into the reaction solution, and maintain the polycondensation time for 18 h to obtain a crude precursor product.

[0096] Decompression step: The crude precursor product was transferred to a 250 mL low-boiling-point removal device, and the device temperature was raised to 165 °C at -99.5 kPa to remove tetrahydrofuran and excess silicon tetrachloride in the crude precursor product. When no small molecules were distilled out of the device, the low-boiling point removal operation was stopped; after the material was cooled to room temperature, residual chloride ions were removed by filter pressing, and 1.87 g of pre-dried 4A molecular sieve was added to the filtrate to remove residual chloride ions. After filtration, 33.42 g of colorless, clear and transparent cross-type polysiloxane with a terminal dimethylhydrogensiloxy group was obtained, with a yield of 85.20%. Its H NMR spectrum is shown in the attached figure. Fig.10 As shown, 1 H NMR (400 MHz, Chloroform-d) δ=0.09 (s, 985H), δ=4.70 (s, 4H).

[0097] Catalytic step: under the protection of dry nitrogen, 25 mL of toluene, 0.013 g of 2,6-di-tert-butyl-4-methoxyphenol (BHT), 0.59 g of 1,2-epoxy-4-vinylcyclohexane and 0.90 g of a platinum catalyst having a platinum atomic content of 0.02 wt% were added to a 100 mL three-necked flask, the temperature was raised to 90 °C under stirring, and the mixture was activated for 0.5 h; 12.00 g (0.00098 mol) of the cross-shaped polysiloxane obtained in the decompression step was added dropwise to the three-necked flask, the dropping time was controlled to be 1.5 h, the catalytic temperature was maintained at 90 °C after the addition was completed, the reaction was stopped after 6 h of catalysis, and a reaction mixture was obtained.

[0098] Removal step: The reaction mixture was cooled to room temperature and then transferred to a low boiling point removal device. Under the protection of dry nitrogen gas with a moisture content of less than 100 ppm, the removal pressure was -100.2 kPa, and the temperature was gradually raised to a removal temperature of 130 °C. After the solvent was removed under reduced pressure and cooled to room temperature, 10.99 g of an amber cross-shaped silicone resin with an alicyclic epoxy functional group as the terminal group was obtained. The yield was 88.0%. Its H NMR spectrum ( 1 H NMR) as attached Fig.11 shown. 1 H NMR (400 MHz, Chloroform-d): δ=0.05 (s, 337H), δ=0.49 (t, 2H), δ=1.82 (m, 1.2H), δ=3.13 (m, 1.4H).

[0099] Performance Testing

[0100] 5.0 g of the cross-shaped silicone resin prepared in Example 1 was mixed evenly with 0.25 g of a UV cationic photocuring initiator triarylsulfonium hexafluoroantimonate and placed in a drawer-type UV light curing machine (power 2.2 kW), and cured under UV light for 20 s to obtain a cross-linked silicone resin sample 1. The cross-shaped silicone resins prepared in Examples 2 to 5 were prepared in the same manner to obtain cross-linked silicone resin samples 2 to 5.

[0101] The obtained silicone resin samples 1 to 5 were subjected to thermal gravimetric performance tests (TGA) in a nitrogen atmosphere using Discovery TGA from TA Company of the United States. The test temperature range was 40 to 800 °C, the carrier gas flow rate was 30 mL / min, and the heating rate was 20 K / min. The thermal gravimetric curves of each sample in a nitrogen atmosphere are shown in the attached figure. Fig.12 As shown, these samples lost 5% weight (T 5% )、10%(T 10% )、20%(T 20% ), and 50%(T 50% ) are shown in Table 1. The temperature T of each sample at the maximum thermal degradation rate MRDT The corresponding maximum thermal degradation rates MRDT are also listed in Table 1.

[0102] Table 1 Nitrogen TGA test results of silicone resin samples 1 to 5

[0103]

[0104] It can be seen from the data in Table 1 that the cross-shaped silicone resin with alicyclic epoxy functional groups as the terminal group prepared by the present invention can not only be quickly cross-linked and cured under UV cationic photoinitiator, but also the cured product has excellent thermal properties, which can meet the requirements of packaging materials for high heat resistance environment.

[0105] The cross-shaped silicone resin of the present application, whose terminal group is an alicyclic epoxy functional group, is prepared through a condensation step, a decompression step, a catalysis step and a removal step. The material mixed with a UV cationic photocuring initiator can be quickly cross-linked and cured under UV light to avoid damage to the device caused by thermal curing; and the formed three-dimensional network structure of the silicone resin has better curing degree, toughness and thermal properties, broadens its application field, and gives the packaged integrated circuits and electronic components a higher operating temperature.

[0106] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A silicone resin, characterized in that: Its structural formula is shown in the following formula (I): (Ⅰ) Where m is any positive integer from 0 to 50; The preparation method of the silicone resin comprises a polycondensation step, a decompression step, a catalysis step and a removal step. The polycondensation step is: in an inert gas atmosphere, add polydimethylsiloxane, the structure of which is shown in the following formula (II), into a container, then add a solvent and a tetrafunctional organosilicon monomer to carry out a polycondensation reaction to obtain a crude precursor product. (Ⅱ) Where m is a positive integer from 0 to 50; The decompression step is to remove the solvent and low molecular weight substances in the crude precursor product to obtain polysiloxane, the structure of which is shown in the following formula (III): (Ⅲ) Where m is any positive integer from 0 to 50; The catalytic step is: in the inert gas atmosphere, reacting the alicyclic epoxy reaction monomer containing a C=C double bond, the polysiloxane and the catalyst in a solvent to obtain a crude reaction product; The removal step comprises: removing the solvent and small molecule impurities from the crude reaction product to obtain the silicone resin; In the polycondensation step, the mass ratio of the polydimethylsiloxane to the volume ratio of the solvent is 191:300; the molar ratio of the polydimethylsiloxane to the tetrafunctional silicone monomer is 41:12; In the polycondensation step, the tetrafunctional organosilicon monomer is silicon tetrachloride; An antioxidant is also added in the catalytic step, and the mass ratio of the antioxidant to the alicyclic epoxy reaction monomer containing a C=C double bond is (0.001:1) to (0.1:1); In the catalytic step, the mass ratio of the solvent to the alicyclic epoxy reaction monomer containing a C=C double bond is (10:1) to (40:1); the molar ratio of the polysiloxane to the alicyclic epoxy reaction monomer containing a C=C double bond is (0.15:1) to (0.40:1).

2. The silicone resin according to claim 1, characterized in that In the decompression step, a molecular sieve is used to remove residual chloride ions. The molecular sieve is a 4A type molecular sieve, and the amount of the molecular sieve used is 1% to 10% of the mass of the crude precursor product.

3. The silicone resin according to claim 1, characterized in that: In the catalytic step, the catalyst is a platinum catalyst, and the ratio of the mass of the platinum atoms in the platinum catalyst to the mass of the polysiloxane and the alicyclic epoxy reaction monomer containing a C=C double bond is (5×10 -6 :1) ~ (500×10 -6 :1).

4. The silicone resin according to claim 1, characterized in that The alicyclic epoxy reaction monomer containing C=C double bonds is 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-3-vinylcyclohexane, 3-(1-methylvinyl)-7-oxabicyclo[4.1.0]heptane, 2-methyl-5-(1-methylvinyl)-7-oxabicyclo[ 4.1.0] a combination of one or more of heptane; An antioxidant is also added in the catalytic step, and the antioxidant is a combination of one or more of 2,6-di-tert-butyl-4-methoxyphenol, p-hydroxyanisole, phenothiazine, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

5. A conformal coating, characterized in that: The invention comprises component A and component B, wherein component A is the silicone resin according to any one of claims 1 to 4, and component B is a UV curing agent.

Citation Information

Patent Citations

  • SU435241A1